2021
DOI: 10.1108/arj-03-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multi-industry directorship on firm performance: a study with reference to India

Abstract: Purpose This study aims to reconcile the contradictory findings of multiple directorships (MD) and its impact on firm performance. The present work incorporates the industry experience of busy directors into the picture and examines its impact on firm performance. Design/methodology/approach Data are collected for 345 non-financial National Stock Exchange listed firms from Bloomberg, Centre for Monitoring Indian Economy ProwessIQ database and company annual reports from the financial year 2008–2009 to 2017–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 91 publications
2
7
0
Order By: Relevance
“…An individual may see high levels of board activity as a possible threat to the effectiveness of corporate oversight and the overall profitability of the organization (Mohapatra and Mishra, 2021).…”
Section: H3mentioning
confidence: 99%
See 1 more Smart Citation
“…An individual may see high levels of board activity as a possible threat to the effectiveness of corporate oversight and the overall profitability of the organization (Mohapatra and Mishra, 2021).…”
Section: H3mentioning
confidence: 99%
“…(Clark et al, 2021;Arora, 2022) Board Busyness "Board Busyness divided by the total number of board directors". (Mohapatra and Mishra, 2021) Board Independence "Percentage of independent directors on the board". (Norliana et al, 2018)…”
Section: Independent Variablementioning
confidence: 99%
“…However, the influence of ownership structure and the presence of BIG4 auditors exhibit a significant role in both IC and FP (Bamiatzi et al 2014;Cerbioni and Parbonetti 2007;Purkayastha et al 2022). The ownership structure in the Indian environment is highly complex due to the dominance of business group firms (Mohapatra and Mishra 2021;Purkayastha et al 2022). Although the group affiliation has certain benefits, like access to organizational assets and internal capital from the parent company that helps improve the FP, the same is coupled with disadvantages, such as principal-principal agency conflict, i.e., conflict of interest between major and minority shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of a compulsory reporting requirement, prominent Indian corporations such as Reliance Industries, TCS, and ITC have adopted the practice of including their IC as an integral element in their annual reports. So, the above dynamics relating to IC and the unique Indian setting due to distinct accounting practices and complex ownership structure (Mohapatra and Mishra 2021;Purkayastha et al 2022) motivate this study to investigate deeper to examine the identified research gaps.…”
Section: Introductionmentioning
confidence: 99%
“…The board of directors is a cornerstone internal corporate governance mechanism responsible for monitoring the quality of the firm’s financial statements (Loukil et al , 2019). It has the legal authority to monitor and approve managerial activities, evaluate the performance of executive managers and reward or punish that performance (Mohapatra and Mishra, 2021). Likewise, the board of directors protects the interests of shareholders and other stakeholders (Jensen and Meckling, 1976; Fama, 1980; and Fama and Jensen, 1983).…”
Section: Introductionmentioning
confidence: 99%